Susceptibility and Pathology in Juvenile Atlantic Cod Gadus morhua to a Marine Viral Haemorrhagic Septicaemia Virus Isolated from Diseased Rainbow Trout Oncorhynchus mykiss - Nina Sandlund; Renate Johansen; Ingrid U. Fiksdal; Ann Cathrine B. Einen; Ingebjørg Modahl; Britt Gjerset; Øivind Bergh (Animals, 2021)
The first known outbreak caused by a viral haemorrhagic septicaemia virus (VHSV) strain of genotype III in rainbow trout occurred in 2007 at a marine farm in Storfjorden, Norway. The source of the virus is unknown, and cod and other marine fish around the farms are suspected as a possible reservoir. The main objective of this study was to test the susceptibility of juvenile Atlantic cod to the VHSV isolate from Storfjorden. As the pathology of VHS in cod is sparsely described, an additional aim of the study was to give a histopathological description of the disease. Two separate challenge experiments were carried out, using both intra peritoneal (ip) injection and cohabitation as challenge methods. Mortality in the ip injection experiment leveled at approximately 50% three weeks post challenge. Both immunohistochemical and rRT-PCR analysis of organs sampled from diseased and surviving fish confirmed VHSV infection. No VHSV was detected in the cohabitants. The results indicate that Atlantic cod has a low natural susceptibility to this VHSV genotype III strain. One of the most extensive pathological changes was degeneration of cardiac myocytes. Immunohistochemistry confirmed that the lesions were related to VHSV. In some fish, the hematopoietic tissue of spleen and kidney showed degeneration and immunostaining, classical signs of VHS, as described in rainbow trout. Positive immunostaining of the capillaries of the gills, suggests this organ as a useful alternative when screening for VHSV.